Hiking motivation and constraints: a case study among students in Universiti Putra Malaysia - Zakri, Nur Alia (2019)
Hiking is a recreational activity that uses physical and mental strength which contribute to various benefits to individuals and society. Motivation such as fitness level, scenic beauty and supportive environment are important to encourage one’s participation in hiking activities. The study aimed to determine motivation and constraints of students in Universiti Putra Malaysia to participate in hiking activities. A comparison between natural science based students and non-natural science based students were also conducted. A total of 253 sets of questionnaires were distributed to UPM students. Questionnaire administered was developed based on Maslow's Hierarchy of Needs, and covers different scope including motivation, constrains, and recommendations from respondents. Results were obtained by using descriptive and t-test analysis. The results showed that scenic beauty is the most important motivation that encourage students’ participation in hiking activities, with mean value of 4.69. Result also showed that major constraint that limits students’ participation is physical abilities with mean value of 4.01. Furthermore, a comparison between natural science based and non-natural science based students indicated an interesting finding. The result highlighted that there are significant differences in the motivation factor where non-natural science based students have higher motivation to participate in hiking activities in terms of time, relaxation, healthy lifestyle and physical fitness. The comparison suggested that education background does not influence students’ motivation in hiking activities.